Late Pleistocene - Holocene Paleoecology of Southern Mesopotamia, Iraq - S. Al – Sheikhly, Saad; A. Al – Jumaily, Wajih; S. Al - Ka’abi, Fouad; Kh. Al – Shehmany, Zaid; A. Owen, Munif (Iraqi Journal of Science, 2021)
The distributions of rivers, back swamps, delta, and ancient marine shore line of Southern Mesopotamia during Late Pleistocene – Holocene have been studied depending on the ostracoda and foraminifera assemblages as ecological indicators to determine the ecofacies and paleosalinities, which diagnose different depositional environments. The data are collected from 86 boreholes (including 12 deep boreholes), covering almost the entire Southern Mesopotamia.Rates of sedimentation are calculated and corrected for compaction in this study, relative to previously measured C14 dating by some authors, for the marine and non- marine (Ur Flood) deposits.Those rates of sedimentation found in this study are varies from a borehole to another, according to the environment of deposition; fluvial, back swamps, deltaic or marine environments.The base of the Ur Flood bed is considered as a marker for correlations between the studied boreholes, and to distinguish the successive depositional cycles basing on their faunal content of ostracoda and foraminifera.Accordingly, nine paleoecological maps for the Southern Mesopotamia are made to represent the age intervals between 22000 B.P. to 1000 B.P., showing the distribution of ancient rivers, back swamps, delta and ancient marine shore line.